Mechanism of unprecedented hydroxyl radical production and site-specific oxidative DNA damage by photoactivation of the classic arylhydroxamic acid carcinogens. (8th January 2019) - Xu, Dan; Huang, Chun-Hua; Xie, Lin-Na; Shao, Bo; Mao, Li; Shao, Jie; Kalyanaraman, Balaraman; Zhu, Ben-Zhan
Abstract: The carcinogenicity of N -hydroxy-2-acetamidofluorene ( N -OHAAF), the major genotoxic metabolite of the classic model aromatic amine (AA) carcinogen 2-acetylaminofluorene, has been attributed mainly to the formation of DNA adducts via arylnitrenium upon enzymatic activation. Here, we show, unexpectedly, that exposure of N -OHAAF to UV or sunlight irradiation can not only induce the formation of the well-known covalent DNA adducts, but, more interestingly, simultaneous generation of oxidative DNA damage was also observed as measured by the formation of DNA single-/double-strand breaks (SSBs/DSBs) and 8-oxo-2′-deoxyguanosine (8-oxodG), which were partly inhibited by the typical hydroxyl radical ( OH) scavengers. Electron spin resonance spin-trapping and fluorescent studies unequivocally confirmed that the highly reactive OH was generated from photolysis of N -OHAAF. Further DNA sequencing investigations suggest that photoactivation of N -OHAAF caused preferential cleavage at guanine, thymine and cytosine sites. More importantly, the formation of 8-oxodG and DSBs were also observed when fibroblast Balb/c-3T3 cells were co-exposed to N -OHAAF/UV irradiation as measured by double immunofluorescence staining. Taken together, we propose that both OH and amidyl radicals can be readily produced via N–OH homolysis in N -OHAAF by photoirradiation, which can induce both oxidative and covalent DNA damage. This represents the first report of OH production and site-specific DNA damage via photoactivation of the genotoxic hydroxamic acid intermediate, which provides a new free radical perspective to better understand the molecular mechanism for the carcinogenicity of AAs. Abstract : N -OHAAF can be photoactivated to induce both covalent and oxidative DNA damage. Reactive OH produced by N -OHAAF/irradiation is responsible for site-specific DNA damage. This study provides a novel radical perspective for aromatic amines' carcinogenicity.